(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The formation of a culture of speech for Primary School students is an important part of the educational process. The culture of speech is the ability of a person to express his thoughts clearly, fluently and intelligibly. From the beginning of their schooling, children share their thoughts with others through speech, ask questions, prepare answers, and communicate. Therefore, the formation of a culture of speech is one of the main tasks in the elementary grades. This process involves not only improving language knowledge, but also teaching culture, etiquette and rules of communication.